A Mobility Aware Schema To Lower Packet Losses For Reactive Ad Hoc Routing Protocols - Ilyas Bambrik; Didi Fedoua (Universitas Islam Sultan Agung, 2016)
In an increasingly wireless world, Ad hoc networks have progressively been developed to become a suitable replacement or, at least complement to the traditional wireless networks. In contrast to the conventional wireless network, the Ad hoc network does not necessarily need a preset infrastructure to be functional. The network members move freely and arrange themselves to perform the routing operations in a distributed fashion. The kernel technology enabling such flexibility is the routing protocol. Though the absence of the infrastructure lowers the installation, configuration and maintenance cost of the dynamic networks, the mobile nodes must deal with several complex issues. Thus, managing : a) security, b) power consumption and balance, c) Quality of Service, in a distributed manner is very challenging. However, above all else, maintaining a path formed by moving particles is the most problematic task. In this paper we analyse the effect of the nodes mobility on the routing protocol performance. Then, we propose a simple schema to counter this issue.